Methodology for assessment of repair and restoring potential of real estate - Avilova, I P; Naumov, A E; Ursu, I V; Abakumov, R G (IOP conference series. Materials Science and Engineering, 2019)
Buildings and structures, as complex technological objects ensuring the effective functioning of a number the urban development environment social processes, need periodically technical updating, conceptually viewed from the standpoint of expedient reconstruction. The respective budgets rational strategic and operational planning issues directed to the immovable complexes' reconstruction should be considered from the standpoint of both technical and town-planning expediency of reconstruction determined by a number of the object key indicators of reconstruction forming its urban-planning reconstruction potential. Particularly acute is the reconstruction rationality quantitative assessment question when implementing the investment programs financed by municipal and federal budgets, in which the integrated reconstruction of the territory is most effective. The reconstruction resource intensity is made up of the territory individual objects local resources - interrelated territorial functions carriers. The methodological approaches and algorithms for constructing a quantitative assessment of the property repair and restoration potential can be an effective complement to methods of dynamic analysis and the urban planning potential effectiveness evaluation of the actively developed territories. The paper demonstrated the practical use examples of the proposed methodologies, proposed methodological approaches to their integration into practical software industry.